Mechanical, Thermal and Morphological Properties of PLA/PP Melt Blends - Mohd Bijarimi, Mat Piah; Sahrim, Ahmad; Rozaidi, Rasid (2012)
In this study, polylactic acid (PLA) was melt blended with polypropylene (PP) and liquid natural rubber (LNR) with the ratio of PLA/PP (90/10) and PLA/PP/LNR (90/10/10) in the Haake Rheomix internal mixer. The mechanical properties of such as stress-strain, flexural and impact were studied. It was found that the elongation at break, flexural and notched impact strength increased significantly for the LNR compatibilized PLA/PP blend. The DSC and FTIR showed the PLA/PP and PLA/PP/LNR were not miscible.